Taxation and Foreign Direct Investment: A Synthesis of Empirical Research - Ruud A. de Mooij; Sjef Ederveen (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper reviews the empirical literature on the impact of company taxes on the allocation of foreign direct investment. We make the outcomes of 25 empirical studies comparable by computing the tax rate elasticity under a uniform definition. The mean value of the tax rate elasticity in the literature is around -3.3, i.e. a 1%-point reduction in the host-country tax rate raises foreign direct investment in that country by 3.3%. There exists substantial variation across studies, however. By performing a meta analysis, the paper aims to explain this variation by the differences in characteristics of the underlying studies. Systematic differences between studies are found with respect to the type of foreign capital data used, and the type of tax rates adopted. We find no systematic differences in the responsiveness of investors from tax credit countries and tax exemption countries.
Keywords: F21; H25; 330